352 Efficacy and safety of abrocitinib in Chinese patients with moderate-to-severe atopic dermatitis: a post-hoc analysis of the JADE REGIMEN phase 3 trial. (25th January 2023) - Li, Hang; Cheng, Hao; Lu, Qianjin; Lai, Wei; Tao, Xiaohua; Encinas, Gerardo A; Vyas, Shefali; Wang, Bo; Luo, Xin; Li, Shiqi
Abstract: In the multicenter induction, randomized withdrawal, and retreatment phase 3 JADE REGIMEN trial (NCT03627767), abrocitinib demonstrated efficacy and was well tolerated in patients with moderate-to-severe atopic dermatitis (AD). To analyze data from Chinese patients who were enrolled in the JADE REGIMEN trial with the aim of further characterizing the efficacy and safety of abrocitinib in Chinese patients with moderate-to-severe AD. In JADE REGIMEN, patients aged ≥12 years with moderate-to-severe AD who responded to abrocitinib 200 mg during open-label induction for 12 weeks (defined as achieving an Investigator Global Assessment score of 0 [clear] or 1 [almost clear] with a ≥ 2-grade improvement from baseline [IGA 0/1] and a ≥ 75% improvement from baseline on the Eczema Area and Severity Index [EASI-75]), were randomly assigned 1 : 1:1 to blinded abrocitinib 200 mg, abrocitinib 100 mg or placebo for 40 weeks (maintenance period). Patients who experienced a flare in the maintenance period (defined as a ≥ 50% loss of initial EASI response at week 12 with a new IGA score ≥2) entered a 12-week open-label rescue period of abrocitinib 200 mg with medicated topical therapy. This analysis included data from Chinese patients enrolled in mainland China; evaluated endpoints were the probability of flare and median time to flare during the maintenance period and ≥75% improvement from rescue baseline on the EASI (recapture of EASI-75 response) at week 12 of the rescue period. Safety was assessed by adverse event monitoring. Of 1233 patients treated in the induction period, 118 were enrolled from China (median age [interquartile range, IQR], 24.0 [19.0–31.0] years; median duration since onset of AD [IQR], 8.0 [3.0–11.3] years). At week 12 of the induction period, 82 (69.5%), 83 (70.3%), 100 (84.7%) and 70 (67.3%) patients achieved IGA 0/1 and EASI-75; IGA 0/1; EASI-75; and a ≥ 4-point improvement from baseline in Peak Pruritus Numerical Assessment Scale (PP-NRS4; used with permission from Regeneron Pharmaceuticals, Inc., and Sanofi), respectively, consistent with the overall JADE REGIMEN population. A total of 81 (68.6%) patients were randomly assigned to the maintenance period (median age [IQR], 22.0 [18.0–30.0] years). At week 52, the probability of experiencing a flare was 13.8% (95% CI, 5.4–32.7), 41.5% (25.4–62.4) and 76.0% (55.7–91.8) in the abrocitinib 200 mg, abrocitinib 100 mg and placebo arms, respectively. The median time to flare was 28.5 (95% CI, 22–119) days and 323 (154–323) days in the placebo and abrocitinib 100 mg treatment arms, respectively. It was not possible to estimate the median time to flare in the abrocitinib 200 mg treatment arm because too few flaring events ( n = 4) were reported in that group. At the end of the maintenance period, the proportions of Chinese patients in both abrocitinib treatment arms who maintained IGA 0/1, EASI-75 and PP-NRS4 responses achieved during induction were consistent with those observed in the overall population. After 12 weeks of rescue treatment, 75% of all Chinese patients who experienced a flare recaptured the EASI-75 response. In the maintenance period, 86.2% and 71.9% of Chinese patients experienced adverse events in the abrocitinib 200 and 100 mg arms, respectively. No new safety signals were identified in patients from China compared to the overall population; there were no adjudicated malignancy events and no deaths. The results of this post-hoc analysis of patients from China were consistent with the overall JADE REGIMEN study population. Induction with abrocitinib 200 mg and continuous or reduced-dose maintenance with abrocitinib 200 or 100 mg were effective in reducing the risk of flare and were well tolerated in Chinese patients. Rescue treatment effectively recaptured response in most patients who experienced a flare.